2003
DOI: 10.1345/aph.1d183
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Intervention Enhances Adherence to Orlistat Therapy

Abstract: In this pilot study, patients receiving pharmaceutical care took orlistat longer than the controls and had improved outcome with orlistat therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 10 publications
1
64
0
Order By: Relevance
“…22 29 However, it should be noted that attendance rates on the programme were better at pharmacies than at GP providers. The demographic characteristics of participants had no discernible impact on completion rates.…”
Section: Almost Two-thirds Of Participants Enrolled On the My Choice mentioning
confidence: 99%
“…22 29 However, it should be noted that attendance rates on the programme were better at pharmacies than at GP providers. The demographic characteristics of participants had no discernible impact on completion rates.…”
Section: Almost Two-thirds Of Participants Enrolled On the My Choice mentioning
confidence: 99%
“…Similarly, socio-economic conditions like the patients' beliefs regarding the disease and treatment, inaccessibility of the treatment, and the patients' unaffordability to the treatment are also associated with the cases of non-complaince [5,17]. Non-compliance prevails if the patient is unaware of his/ her disease state, the benefits of the prescription therapy, and the consequences of non-compliance [12][13][14]. Beside these, some behavioural researches have shown that factors like the forgetfulness of the patient to use or refill the medicines, the direction of the medicine use and the experiences of bad side effects result in non-compliance to the treatment [15,20,21].…”
Section: Patient Related Factorsmentioning
confidence: 99%
“…The regular prescribing behaviours, the time which is spent by the patients in the doctors' cabins and the influence of the pharmaceutical companies on the prescribing behaviours of clinicians, have been associated with the cases of non-complaince [22]. The counseling behaviours and the dispensing behaviours (including labelling) of the pharmacists are two major causes which may have a direct influence on the compliance of the patients towards their therapies [10,13].…”
Section: Patient Related Factorsmentioning
confidence: 99%
See 2 more Smart Citations